The Influence of Exercise on Cardiovascular Health in Sedentary Adults With Human Immunodeficiency Virus. Issue 3 (May 2018) - Webel, Allison R.; Perazzo, Joseph; Longenecker, Christopher T.; Jenkins, Trevor; Sattar, Abdus; Rodriguez, Margaret; Schreiner, Nate; Josephson, Richard A.
Abstract : Background: Lifestyle physical activity (ie, moderate physical activity during routine daily activities most days of the week) may benefit human immunodeficiency virus (HIV)–positive adults who are at high risk for cardiovascular disease. Objective: The aims of this study were to describe lifestyle physical activity patterns in HIV-positive adults and to examine the influence of lifestyle physical activity on markers of cardiovascular health. Our secondary objective was to compare these relationships between HIV-positive adults and well-matched HIV-uninfected adults. Methods: A total of 109 HIV-positive adults and 20 control participants wore an ActiGraph accelerometer, completed a maximal graded cardiopulmonary exercise test, completed a coronary computed tomography, completed anthropomorphic measures, and had lipids and measures of insulin resistance measured from peripheral blood. Results: Participants (N = 129) had a mean age of 52 ± 7.3 years, 64% were male (n = 82), and 88% were African American (n = 112). On average, HIV-positive participants engaged in 33 minutes of moderate-to-vigorous physical activity per day (interquartile range, 17–55 minutes) compared with 48 minutes in controls (interquartile range, 30–62 minutes, P = .05). Human immunodeficiency virus–positive adults had poor fitness (peak oxygen uptake [VO2 ], 16.8 ± 5.2 mL/min per kg; and a ventilatory efficiency, 33.1 [4.6]). A marker of HIV disease (current CD4+ T cell) was associated with reduced peak VO2 ( r = −0.20, P < .05) and increased insulin resistance ( r = 0.25, P < .01) but not with physical activity or other markers of cardiovascular health ( P ≥ 0.05). After controlling for age, gender, body mass index, and HIV status, physical activity was not significantly associated with peak VO2 or ventilatory efficiency. Conclusion: Human immunodeficiency virus–positive adults have poor physical activity patterns and diminished cardiovascular health. Future longitudinal studies should examine whether HIV infection blunts the beneficial effects of physical activity on cardiovascular health.